Key stages in mammary gland development - The alveolar switch: coordinating the proliferative cues and cell fate decisions that drive the formation of lobuloalveoli from ductal epithelium - Oakes, Samantha R (BioMed Central, 2006)
Massive tissue remodelling occurs within the mammary gland during pregnancy, resulting in the formation of lobuloalveoli that are capable of milk secretion. Endocrine signals generated predominantly by prolactin and progesterone operate the alveolar switch to initiate these developmental events. Here we review the current understanding of the components of the alveolar switch and conclude with an examination of the role of the ets transcription factor Elf5. We propose that Elf5 is a key regulator of the alveolar switch.